THE RELIABILITY MODEL OF A SELECTED CLASS OF THE HIERARCHICAL SYSTEMS - Jozwiak, I. J. (Periodica Polytechnica Mechanical Engineering, 1989)
The paper analyses digital systems a with three-level hierarchical structure. It has taken intoaccount reliability and functional aspects of the system. A reliability-functional model of the proposeddigital system has been presented.